2020
DOI: 10.18203/2320-1770.ijrcog20201225
|View full text |Cite
|
Sign up to set email alerts
|

A study of maternal and fetal outcomes in critically ill obstetric patients

Abstract: Background: Pregnancy related morbidity is becoming a nightmare in Indian women. Some of these women end up in mortality and a few of them narrowly escape death. Critical care should be and is an authenticated part of obstetric practice. This study is an effort initiated to understand the risk of maternal morbidity, to investigate the contributing factors, foetal outcome, to study the adverse event, cause of maternal death and remedial measures. Methods: All the obstetric cases admitted in Intensive care unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Of the critically ill pregnant women, maternal mortality was 12.8% and fetal mortality was 40.8%. 4 In another recent study of 91 pregnant ICU patients (26 per 1,000, i.e., 2.6%) by Sailaja and Renuka, 5 almost similar findings were noted. Being a tertiary care center, most patients were postpartum (84.6%) and referred to ones (63.8%).…”
Section: Linical P Rofile Of the mentioning
confidence: 58%
See 1 more Smart Citation
“…Of the critically ill pregnant women, maternal mortality was 12.8% and fetal mortality was 40.8%. 4 In another recent study of 91 pregnant ICU patients (26 per 1,000, i.e., 2.6%) by Sailaja and Renuka, 5 almost similar findings were noted. Being a tertiary care center, most patients were postpartum (84.6%) and referred to ones (63.8%).…”
Section: Linical P Rofile Of the mentioning
confidence: 58%
“…This was highlighted in a recent study of more than 10,000 deliveries, by Tasneem and Sharma. 4 They found that anemia prevailed in 25.5% of cases. Among 110 critically ill, out of 10,208 parturients, the main indications for intensive care unit (ICU) admission in their study were disseminated intravascular coagulation (DIC) (39%), eclampsia (22.7%), peri partum hemorrhage (PPH) (21.8%), hemolysis elevated liver enzymes and low platelets syndrome (HELLP) (13.6%), acute renal failure (10.1%), acute respiratory distress syndrome (ARDS) (3.6%), and sepsis (3.2%).…”
Section: Linical P Rofile Of the mentioning
confidence: 97%